Synthesis of Migrastatin and its Macroketone Analogue and In Vivo FRAP Analysis of the Macroketone on E‐Cadherin Dynamics. Issue 10 (11th June 2014) - Lo Re, Daniele; Zhou, Ying; Nobis, Max; Anderson, Kurt I.; Murphy, Paul V.
Abstract An efficient and scalable synthesis of a key acyclic intermediate used for the preparation of migrastatin and its macroketone analogue is described; Brown alkoxyallylation is the key step for this synthesis. The macroketone was prepared on 100 mg scale by this route. Treatment of invasive pancreatic cancer cells grown on a cell‐derived matrix or as subcutaneous tumours in nude mice with the macroketone inhibited E‐cadherin dynamics in a manner consistent with increased cell adhesion and reduced invasive potential.